Implementasi forecastHybrid Package menggunakan R Studio Cloud untuk Prediksi Pertumbuhan Dana Pihak Ketiga dan Pembiayaan Pada Bank Muamalat Indonesia - Niken Probondani Astuti; Rizal Bakri (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
This study aims to find out how to forecast the growth performance of third party funds (TPF) and financing which is measured on a quarterly by applied the hybrid method with R Studio Cloud using ‘forecastHybrid’ package. This prediction is expected to provide information and data on the growth of third party fund and financing for Bank Muamalat which is experiencing problems of lack of capital and non-performing funds (NPF). Forecasting with Hybrid methods combines ARIMA auto forecasting methods, exponential smoothing forecasting methods, theta forecasting methods, neural network forecasting methods, seasonal and trend decomposition forecasting methods, and TBATS forecasting methods. The forecast results show that the Hybrid method is able to provide information as a decision-making material for Bank Muamalat